PENGARUH PENGGUNAAN MEDIA ANIMASI STOP MOTION BERDASARKAN TINGKATAN MOTIVASI TERHADAP HASIL BELAJAR SISWA DALAM PEMBELAJARAN SENI RUPA DI MTsN MATUR - FEBRIA RAHMADANI, Drs. Wisdiarman, M.Pd., Drs. Yusron Wikarya, M.Pd. (Universitas Negeri Padang, 2017)
This research aims to (1) Assess the results of the learning motivation of students who have studied high taught with stop motion media different significant learning results with students who have high taught motivation by conventional media in MTsN Matur. (2) Examine the learning results of students who have low motivation are taught using animation stop motion media different significantly with students who low taught motivated by conventional media in MTsN Matur. (3) It examines the results of a study group motivation high and low motivation students in the fine arts taught learning with animation stop motion media different significantly from the results of the Group's motivation high and low motivation of students in learning the fine arts taught in conventional media in MTsN Matur. Research is designed using the experimentation. show results media uses animation stop motion a positive influence on increased study results the fine arts students.Key words: stop motion animation learning, media, learning motivation, learning and results